2008
DOI: 10.1210/jc.2007-2467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Administration of Cross-Sex Hormone Therapy on Serum and Urinary Uric Acid in Transsexual Persons

Abstract: Serum levels of uric acid and the FEUA are altered in transsexuals as a result of cross-sex hormone therapy. The results concerning the MFT group support the hypothesis that the lower levels of uric acid in women are due to estrogen-induced increases in FEUA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
110
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 16 publications
14
110
0
2
Order By: Relevance
“…Estrogen replacement therapy also reduces the serum UA concentrations in hyperuricemic postmenopausal females [11]. With respect to TRT, only two reports have shown that testosterone treatment for female to male gender reassignment leads to increased serum UA concentrations and reduced renal excretion of UA [12,13]. Our current study also demonstrated serum UA upregulation induced by testosterone administration.…”
Section: Figsupporting
confidence: 72%
See 1 more Smart Citation
“…Estrogen replacement therapy also reduces the serum UA concentrations in hyperuricemic postmenopausal females [11]. With respect to TRT, only two reports have shown that testosterone treatment for female to male gender reassignment leads to increased serum UA concentrations and reduced renal excretion of UA [12,13]. Our current study also demonstrated serum UA upregulation induced by testosterone administration.…”
Section: Figsupporting
confidence: 72%
“…We experienced that, when TRT is initiated, testosterone immediately affects the systemic metabolism in female to male GID patients. Although UA is a possible factor that can be influenced by testosterone administration [10][11][12][13], the early effects and dose-dependency of TRT on the serum UA concentration have not been previously determined. As for the effects of testosterone on the serum UA level, we herein report our experience using three TRT doses in the treatment of female to male GID.…”
Section: Blood Sample Measurementsmentioning
confidence: 99%
“…Estrogen increases the excretion of UA, and SUA levels increase after Table 4 Odds ratios for the incidence of hypertension, metabolic syndrome and hypertension with metabolic syndrome according to serum uric acid tertile or the presence of hyperuricemia menopause. 39 The biological mechanism explaining the relationships between estrogen levels and the development of hypertension or MetS has still not been elucidated. Fourth, we could not assess the dietary statuses of our subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, estrogen could promote the excretion of uric acid, which may avoid the accumulation of uric acid and weaken the activation of uricase in male rats. 25,26 As important human milk constituents, nucleotides and their analogs were included in various forms (for example, polymeric nucleotides, oligonucleotides, mononucleotides, and nucleotides). The Coordinated International Expert Group of the European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) recommends the following maximum concentrations for nucleotides added to infant formula: 1.75 mg/100 kcal of CMP, 1.5 mg/100 kcal of UMP, 1.5 mg/100 kcal of AMP, 0.5 mg/100 kcal of GMP, and 1 mg/100 kcal of IMP.…”
Section: Discussionmentioning
confidence: 99%